1987
DOI: 10.1177/002221948702000303
|View full text |Cite
|
Sign up to set email alerts
|

Information Processing Theory and Learning Disabilities

Abstract: The present article reviews some assumptions related to the information processing framework. The major implications of previous articles are reviewed, as well as some conceptual ambiguities related to the role of the automaticity, prior knowledge, and executive functioning in explaining learning disabilities. The ecological validity of the information processing framework, as well as the limitations of differential theories, is discussed. Discussion is also given to: (a) identifying common denominations, (b) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…Levin et al (1991) demonstrated that by the age of 10 to 12 years, most children perform at adult levels on tasks of executive functioning, including the WCST and a delayed alternation task, supporting the findings of earlier studies by Chelune and Baer (1986). Although it has been suggested that performance on measures of executive function is not correlated with IQ (Segalowitz, Unsal, & Dywan, 1992;Welsh et al, 1991), executive dysfunction may contribute to impaired learning skills (e.g., metacognitive skills and stepwise processing) in children with learning disabilities (Swanson, 1987). Downloaded by [University of Chicago Library] at 18:26 19 November 2014 Welsh et al (1991) identified three factors that account for executive function and appear to (¡merge at developmentally different stages.…”
supporting
confidence: 59%
“…Levin et al (1991) demonstrated that by the age of 10 to 12 years, most children perform at adult levels on tasks of executive functioning, including the WCST and a delayed alternation task, supporting the findings of earlier studies by Chelune and Baer (1986). Although it has been suggested that performance on measures of executive function is not correlated with IQ (Segalowitz, Unsal, & Dywan, 1992;Welsh et al, 1991), executive dysfunction may contribute to impaired learning skills (e.g., metacognitive skills and stepwise processing) in children with learning disabilities (Swanson, 1987). Downloaded by [University of Chicago Library] at 18:26 19 November 2014 Welsh et al (1991) identified three factors that account for executive function and appear to (¡merge at developmentally different stages.…”
supporting
confidence: 59%
“…Previous research has demonstrated executive deficits for children with RD on reading and writing tasks, including lack of awareness of necessary strategies for enhancing comprehension of text; inability to choose appropriate strategies; ineffective monitoring of strategies during reading (Cornoldi, 1990;Forrest-Pressley & Waller, 1984); and deficits in the planning, organization, and monitoring of the writing process (Englert, Raphael, Fear, & Anderson, 1988;Wong, Wong, & Blenkinsop, 1989). These observed differences in the performance of children with and without RD on academic casks may often be the consequence of differences in the underlying knowledge of the relevant subject area rather than of actual differences in strategic behavior (Ceci & Baker, 1989;Sternberg, 1985;Swanson, 1987). That is, Downloaded by [La Trobe University] at 18:21 14 June 2016 it may be easier to develop strategies in areas in which one has expertise than in areas in which one is still in the process of acquiring and mastering basic skills.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a number of information-processing models have been proposed as a means of understanding and thinking about the intervention process (e.g. Brown & Campione, 1986;Carroll, 1976;Gagne, 1985;Horton & Berfeld-MiUs, 1984;Nation & Aram, 1977;Posner & McLeod, 1982;Pressley, Goodchild, Fleet, Zajchowski, & Evans, 1987;Samuels, 1987;Swanson, 1987aSwanson, , 1987b. These models have attempted to explain those aspects of information processing that are fixed or not modifiable in the individual as well as those processes that are Downloaded by [University of Glasgow] Deshler and Lenz alterable or subject to the influence of experience or external feedback and intervention.…”
Section: The Strategies Instructional Approachmentioning
confidence: 99%